Screening of Novel Psychoactive Substances in Postmortem Matrices by Liquid Chromatography–Tandem Mass Spectrometry (LC–MS-MS)†. Issue 8 (26th October 2018) - Fagiola, Michael; Hahn, Timothy; Avella, Joseph
Abstract: Novel psychoactive substances (NPS) are newly emerging compounds, natural and synthetic, that are often sold as "legal" alternatives to controlled substances. These substances can include phenethylamines, tryptamines, synthetic cathinones, piperazines and others. Most novel psychoactive substances and similar designer drugs are often based on the chemical backbone of classic drugs of abuse but are not regularly encountered in postmortem casework. These compounds may go undetected in forensic toxicology labs where suitable identification methods for NPS may not exist. In order to keep up with this ever-expanding list of pharmacologically active and toxicologically hazardous substances, there is an increased need for a screening panel suitable for postmortem human samples such as whole blood and urine. In order to address this increased prevalence of NPS, a method was developed and validated to identify 50 NPS in postmortem samples using liquid chromatography triple quadrupole mass spectrometry. The data presented here represents a validated liquid chromatography triple quadrupole mass spectrometry method to qualitatively identify NPS in postmortem samples. The limit of detection for all compounds was set at 2.5 ng/mL. To evaluate the prevalence of NPS in the region, blood and urine specimens from 110 postmortem cases were submitted for analysis based on initial screening results and/or case history. Of those cases, 28% were positive for several NPS, though only a few were included in the cause of death. The robustness of this method proves that it is suitable for the continual addition of newer substances, ensuring up-to-date simultaneous drug detection.